2016
DOI: 10.1246/bcsj.20160316
|View full text |Cite
|
Sign up to set email alerts
|

The pH Dependent Protein Structure Transitions and Related Spin-State Transition of Cytochrome c′ from Alcaligenes xylosoxidans NCIMB 11015

Abstract: The unusual magnetic/spectroscopic properties of Cytochrome c¤ (Cyt c¤) have been discussed, especially concerning the possibility of a quantum mechanically mixed-spin configuration of heme Fe(III). Here, four unique-spin species were identified from the magnetic circular dichroism (MCD) spectra of Cyt c¤ from Alcaligenes xylosoxidans (AxCyt c¤). The electrospray ionization mass spectrometric (ESI-MS) and circular dichroism (CD) spectroscopic data showed the overall conformation of AxCyt c¤ was unchanged, in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 58 publications
(48 reference statements)
8
9
0
Order By: Relevance
“…The SANS profile at pD 1.7 was fit well using the Debye function and gave Rg = 25.7 A, and clearly showed that the structure of Cyt c' transitioned to the unfolded random coil structure. The unfolded random coil structure of Cyt c' at pD 1.7 indicated by the SANS data is consistent with the structure previously proposed based on CD and ESI-MS spectrometry data [33]. The crystallographic structure of Cyt c' from Alcaligenes was suggested to be a dimer, but the association state in solution was unknown [42].…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…The SANS profile at pD 1.7 was fit well using the Debye function and gave Rg = 25.7 A, and clearly showed that the structure of Cyt c' transitioned to the unfolded random coil structure. The unfolded random coil structure of Cyt c' at pD 1.7 indicated by the SANS data is consistent with the structure previously proposed based on CD and ESI-MS spectrometry data [33]. The crystallographic structure of Cyt c' from Alcaligenes was suggested to be a dimer, but the association state in solution was unknown [42].…”
Section: Resultssupporting
confidence: 88%
“…The Kratky plot of Cyt c' at pD 1.7 shows an intensified plateau region in the high-Q region, without a bell-shaped profile in the low-Q region (Figure 4A), strongly suggesting that Cyt c' becomes a very flexible random coil structure, in good agreement with the Debye function analysis and previous CD and ESI-MS experiments [33]. The Kratky plots of Cyt c' at pD 6.4 and 9.6 (Figure 4B and 4C) are clearly bell-shaped profiles centered at Q = 0.1 Å -1 with a plateau shape in the higher-Q region (Q > 0.2 Å -1 ), indicating a flexible moiety in the protein structure.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Taking advantage of these detection properties, the ESI‐MS has been applied to probe both conformational change and binding/releasing the cofactor in various proteins . Recently, we reported the regulation of heme properties in cytochrome c ′ on the basis of structural information from ESI‐MS . The unfolding of azurin and amicyanin has been studied previously using ESI‐MS.…”
Section: Introductionmentioning
confidence: 99%